The effects of solvents on the physical and electrochemical properties of potassium-ion conducting polymer gel electrolytes. (February 2023) - Madhani, Vaishali; Rathore, Mahendra Singh; Kumar, Deepak
The aim of present work is to investigate the effect of different solvent mixed within poly (vinylidiene fluoride-hexafluoropropylene) (PVDF-HFP) based Potassium ion conducting polymer gel electrolytes. The samples are prepared using solution casting method and the comparative behavior of adding carbonate and glyme in PVDF-HFP/KClO4 matrix is investigated. Subsequently, polymer gel electrolytes are characterized using X-ray diffractometer to analyze the structural features of the electrolyte films. The XRD results reveal that the prepared electrolyte films using both solvents demonstrate semi-crystalline nature. The surface morphology is studied using scanning electron microscopy and significant changes in surface morphology of the polymer gel electrolyte films is observed on introducing carbonate and glyme solvents. Thermal properties and effects of temperature on the prepared electrolytes is examined using differential scanning calorimetry and investigations reveal significant effect of temperature on the heat flow into the polymer gel electrolytes samples. The weight loss of the electrolyte samples with temperature is studied using Thermogravimetric analysis and it is observed that carbonate and glyme based electrolyte offer weight loss of about 7–8 %. The ionic conductivity of 2.53×10 −7  Scm −1 and 3.67×10 −4  Scm −1 while electrochemical stability window of ∼2.5 V is obtained for both polymer gel electrolytes with carbonate and glyme based solvents. The reversibility of K-ion has been established using cyclic voltammetry measurements.